Stable Aqueous Solutions of Naked Titanate Nanotubes. Issue 12 (28th June 2013) - Zennaro, Lucio; Magro, Massimiliano; Vianello, Fabio; Rigo, Adelio; Mariotto, Gino; Giarola, Marco; Froner, Elena; Scarpa, Marina
Abstract Aqueous solutions of naked nanotubes with Ti concentration up to 10 mM are obtained by hydrothermal synthesis followed by extensive ultrasound treatment. The morphology, surface characteristics, and solution behavior of the solubilized nanotubes are investigated. The time course of the solubilization process driven by ultrasound follows a first‐order kinetic law and is mediated by the competition between Na+ and H+ for surface sites. The dynamics of interaction with small cations (i.e. the sodium ion) is studied by nuclear magnetic resonance spectroscopy and is demonstrated to be a multifaced process, since Na+ is in part free to exchange between the binding sites on nanotubes and the bulk and in part is confined to slowly exchanging nanotube sites. The aqueous titanate nanotube solutions are stable for months, thus opening new perspectives for the use of this material in drug delivery and in homogeneous photocatalysis.